2010
DOI: 10.1128/aem.02715-09
|View full text |Cite
|
Sign up to set email alerts
|

Effect of DNA Extraction Method on the Apparent Microbial Diversity of Soil

Abstract: Four extraction methods, including a novel one, were compared for their efficiencies in producing DNA from three contrasting agricultural soils. Molecular analyses (PCR-denaturing gradient gel electrophoresis [DGGE] and clone libraries) focusing on different microbial groups were used as assessment criteria. Per soil, the DNA yields differed between extraction methods. Clear effects of method on apparent richness and community structure were found. Actinobacterial diversity based on soil DNA produced by two di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 15 publications
1
55
1
3
Order By: Relevance
“…The disadvantages of indirect methods are the longer processing time and lower DNA yields. One recent study demonstrated quantitatively the effect of DNA extraction methods on the microbial diversity of the sampled soil and concluded that the yield and diversity of DNA greatly depends on the extraction method and suggested that the use of a novel extraction method may result in having DNA from a microbial taxon that otherwise would not be identified (Inceoglu, Hoogwout et al 2010). …”
Section: Dna Extractionmentioning
confidence: 99%
“…The disadvantages of indirect methods are the longer processing time and lower DNA yields. One recent study demonstrated quantitatively the effect of DNA extraction methods on the microbial diversity of the sampled soil and concluded that the yield and diversity of DNA greatly depends on the extraction method and suggested that the use of a novel extraction method may result in having DNA from a microbial taxon that otherwise would not be identified (Inceoglu, Hoogwout et al 2010). …”
Section: Dna Extractionmentioning
confidence: 99%
“…Past data on community profiling by T-RFLP and other methods revealed that use of a single method for DNA extraction can significantly underestimate the total number of bacterial ribotypes [23,25,26]. Several DNA extraction methods for diverse communities and habitats are available [19,20,23,25]. Therefore, a combination of different DNA extraction methods and the use of more than one genetic marker are recommended to obtain a more accurate evaluation of the diversity of the target organisms or functional groups [23,25,27,28].…”
Section: Technical Advancements In Data Generationmentioning
confidence: 99%
“…Past data on community profiling by T-RFLP and other methods revealed that use of a single method for DNA extraction can significantly underestimate the total number of bacterial ribotypes [23,25,26]. Several DNA extraction methods for diverse communities and habitats are available [19,20,23,25].…”
Section: Technical Advancements In Data Generationmentioning
confidence: 99%
See 2 more Smart Citations